FAKTOR – FAKTOR YANG MEMENGARUHI PERMINTAAN TANAMAN HIAS DI KOTA BATURAJA KABUPATEN OGAN KOMERING ULU - Intan Putri Dianti, Fifian Permata Sari, Henny Rosmawati (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2026)
Ornamental plants are one of the horticultural products that are currently gaining popularity among the public. Producers and marketers should be able to provide ornamental plants according to consumer desires. Therefore, producers need to observe consumer purchasing behavior, because the characteristics of ornamental plants desired by consumers are not entirely the same as the characteristics of plants produced by producers. This study aims to analyze the factors influencing the demand for ornamental plants in Baturaja City. The method used in this study is a survey method. The sampling method used is the accidental method. The number of samples taken is four respondents from each of 10 ornamental plant businesses, resulting in a total sample of 40 respondents. The data obtained were analyzed using multiple linear regression analysis. The results of the study indicate that the factors influencing the demand for ornamental plants in Baturaja City are ornamental plant prices, consumer income, and consumer preferences.